Residues of acidic chitinase cause chitinolytic activity degrading chitosan in porcine pepsin preparations - Tabata, Eri; Wakita, Satoshi; Kashimura, Akinori; Sugahara, Yasusato; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (Scientific reports, 2019)
Commercially available porcine pepsin preparations have been used for the production of chitooligosaccharides with various biomedical activities. However, the origin of this activity is not well understood. Here we show that the chitosan-degrading activity is conferred by residues with chitinolytic activity of truncated forms of acidic chitinase (Chia) persisting in the pepsin preparation. Chia is an acid-stable and pepsin-resistant enzyme that degrades chitin to produce N-acetyl-D-glucosamine dimer. We found that Chia can be truncated by pepsin under stomach-like conditions while maintaining its enzymatic activity. Similarly to the full-length protein, truncated Chia as well as the pepsin preparations digested chitosan with different degrees of deacetylation (DD: 69-84%) with comparable degradation products. The efficiency was DD-dependent with a marked decrease with higher DD, indicating that the chitosan-degrading activity in the pepsin preparation is due to the chitinolytic activity rather than chitosanolytic activity. We suggest that natural or recombinant porcine Chia are suitable for producing chitooligosaccharides for biomedical purposes.
Keywords: prasata; hydrolýza; koncentrace vodíkových iontů; Pepsin A; Swine; Chitosan; Hydrogen-Ion Concentration; Animals; pepsin A; chitosan; Chitinases; chitinasy; zvířata; Hydrolysis